Disruption of piRNA machinery by deletion of ASZ1/GASZ results in the expression of aberrant chimeric transcripts in gonocytes - Shinya IKEDA; Koki TANAKA; Reiko OHTANI; Akifumi KANDA; Yusuke SOTOMARU; Tomohiro KONO; Yayoi OBATA (The Society for Reproduction and Development, 2022)
In the male germline, the machinery to repress retrotransposons that threaten genomic integrity via the piRNA pathway is established in gonocytes. It has been reported that disruption of the piRNA pathway leads to activation of retrotransposons and arrests spermatogenesis before it enters the second meiosis; however, its effects on gonocytes have not been fully elucidated. In this study, we analyzed the effects of Asz1 deletion, which is a crucial component of the piRNA pathway, on the gonocyte transcriptome. In Asz1-null gonocytes, MIWI2, which is responsible for introducing DNA methylation to retrotransposons in a piRNA-dependent manner, disappeared from the nuclei of fetal gonocytes. Transcriptome analysis revealed that retrotransposons targeted by the piRNA pathway and non-annotated transcript variants were upregulated in gonocytes from neonatal Asz1-/- mice. These non-annotated transcript variants were chimeras generated by joining exons transcribed from retrotransposons and canonical genes. DNA methylation analysis showed that retrotransposons that induce the expression of aberrant chimeric transcripts are not fully methylated. This was consistent with the impaired nuclear localization of MIWI2 in Asz1-null gonocytes. Furthermore, heterogeneity of DNA methylation status in retrotransposons was observed in both gonocytes and their descendants. This suggests that the piRNA system in gonocytes can potentially prevent spermatogenic cell populations bearing aberrant chimeric transcripts from propagating later in spermatogenesis. In conclusion, Asz1 is required to repress retrotransposons and retrotransposon-driven aberrant chimeric transcripts in gonocytes through the piRNA pathway.